Split stress rate plasticity formulation. (5th December 2022) - Dafalias, Yannis F.
Abstract: A novel general constitutive formulation framework of rate independent plasticity is presented where the stress rate tensor is split in two components, and plastic loading is affected separately by each one of these two components in relation to a common loading direction normal to a single smooth yield surface in stress space. This split-stress rate separate effect provides greater flexibility for simulating the material response under combined stress rate components loading. The difficulty arises when loading and unloading events may occur interchangeably between the two stress rate components and special attention is required to avoid irrational results and guarantee continuity of response upon rotation of the total stress rate direction at a loading stress point. The formulation can acquire two different analytical schemes, one more complicated but incrementally linear, while the other is simpler but incrementally nonlinear. The key constitutive ingredient of split stress rate definition is a multifaceted choice, and three options are presented. One option which is of particular interest to granular mechanics, splits the stress rate into a component that changes the stress principal values at fixed principal axes, while the other component does exactly the opposite, i.e., rotates the stress principal axes at fixed principal values. For this option various constitutive ingredients and new concepts are introduced and extensively elaborated, with emphasis on dilatancy, understanding that these elaborations are of an exploratory nature intending to prompt further research along the proposed guidelines.